Oral contraceptive use and awareness among patients in a tertiary level teaching hospital: a questionnaire based observational study - Shaikh, Humera Gafur; Shah, Jui (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Oral contraceptive pills (OCPs) are a widely used method of contraception, yet awareness, adherence, and perceptions surrounding their use vary among individuals. Understanding the knowledge, attitudes, and practices related to OCPs is essential for improving reproductive health education and reducing unintended pregnancies. Methods: An observational study was conducted among participants to assess their awareness, usage patterns, and perceptions of OCPs. Data was collected on demographic factors, knowledge of contraceptive effectiveness, adherence to prescribed regimens, reasons for discontinuation, and sources of information. Participant’s responses were examined to identify trends and gaps in knowledge. Results: The findings indicate that a significant proportion of participants had limited awareness of the different types of OCPs and their correct usage. Many participants lacked knowledge regarding the difference between ‘perfect use’ and ‘typical use,’ which impacts overall efficacy. Common reasons for discontinuation included perceived side effects, misinformation, and accessibility issues. While healthcare providers were a primary source of information, a considerable number of participants relied on non-medical sources, leading to misconceptions. Community perceptions and societal stigma were also identified as influencing factors in OCP acceptance. Conclusions: The study highlights the need for improved educational interventions to bridge knowledge gaps regarding OCPs. Enhancing access to reliable information and addressing misconceptions can contribute to better adherence and acceptance of oral contraceptive use, ultimately improving reproductive health outcomes.